2012
DOI: 10.1038/ncomms2262
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a human mitochondrial NAD kinase

Abstract: NAD kinase is the sole NADP+ biosynthetic enzyme. Despite the great significance of NADP+, to date no mitochondrial NAD kinase has been identified in human, and the source of human mitochondrial NADP+ remains elusive. Here we present evidence demonstrating that a human protein of unknown function, C5orf33, is a human mitochondrial NAD kinase; this protein likely represents the missing source of human mitochondrial NADP+. The C5orf33 protein exhibits NAD kinase activity, utilizing ATP or inorganic polyphosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
147
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(154 citation statements)
references
References 48 publications
(88 reference statements)
4
147
0
Order By: Relevance
“…Though we focused on the effects of inhibiting cytosolic NADK in this study, it is important to consider the newly discovered and characterized mitochondrial NADK (mNADK) (Ohashi et al, 2012;Zhang, 2015). In a previous study, Zhang (2015) found mNADK had lower activity compared with NADK and fact had lower expression in liver tumor samples, in contrast with the overexpression of NADK in a variety of cancer types (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Though we focused on the effects of inhibiting cytosolic NADK in this study, it is important to consider the newly discovered and characterized mitochondrial NADK (mNADK) (Ohashi et al, 2012;Zhang, 2015). In a previous study, Zhang (2015) found mNADK had lower activity compared with NADK and fact had lower expression in liver tumor samples, in contrast with the overexpression of NADK in a variety of cancer types (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Although Pos5 shows a low primary structure homology with the human enzyme, the tertiary structure and the key aminoacids of the NADH binding site appear conserved (Ando et al, 2011). Recently, the human mitochondrial NADH kinase (NADK2) has been identified (Ohashi et al, 2012) and mitochondrial NADP(H) deficiency due to a mutation in NADK2 was also proposed as cause of mitochondrial disorders (Houten et al, 2014). Further studies will be necessary to investigate if the increased resistance of other identified deleted strains is a consequence of Pos5 inactivation or is due to a direct activity of AF.…”
Section: Discussionmentioning
confidence: 99%
“…The NAD(H) kinases are the sole enzymes able to convert NAD(H) to NADP(H) using ATP as a phosphate donor. Such a kinase has been identified recently in mammalian mitochondria (51,52), although a possible functional connection between the kinase and Fe-S cluster biogenesis remains to be determined. By contrast, the corresponding NADH kinase in the yeast mitochondrial matrix, called Pos5, has been characterized, and it seems that NADPH, generated by Pos5, plays an important role in Fe-S cluster biogenesis in yeast mitochondria (17,53).…”
Section: Discussionmentioning
confidence: 99%
“…The reductase is likely to be adrenodoxin reductase, which reduces ferredoxins FDX1 and FDX2 (38,39). The reducing equivalents for this electron transport chain may derive from NADPH (50), and, therefore an NAD(H) kinase may also be required inside mitochondria (17,51). The substrate that receives electrons is unknown but could be the S 0 and/or iron involved in Fe-S cluster intermediate formation (4).…”
Section: Discussionmentioning
confidence: 99%